Isokinetic performance of shoulder external and internal rotators of professional volleyball athletes by different positions - Kim, D.-K.; Park, G.; Kuo, L.-T.; Park, W.-H. (Scientific Reports, 2020)
This study aimed to exam the isokinetic shoulder rotator strength of professional volleyball athletes, by playing positions. This cross-sectional study included a total of 49 healthy male professional volleyball players. We measured the isokinetic strength of the external rotator (ER) and internal rotator (IR) muscles and compared the dominant and non-dominant shoulders at angular speeds of 60°/s and 180°/s. In ER, all positions of players had similar strength between the dominant shoulder and non-dominant shoulders. Conversely, all playing positions except libero had stronger strength in dominant shoulder than that in the non-dominant shoulder. The ER/IR ratio in the dominant shoulder was significantly lower only for the attacker (outside hitter and opposite) at 60°/s and 180°/s (P < 0.0001; P = 0.0028 respectively) and blocker at 60°/s (P = 0.0273) when compared with non-dominant shoulder. Furthermore, the attacker had a lower ER/IR ratio in the dominant shoulder than setter and libero at 60°/s and 180°/s. For elite volleyball players without injury, the dominant shoulder had a higher strength of internal rotation, causing the relative muscle imbalance than the non-dominant shoulder, especially for the attacker and blocker positions. Training program should be individualized for each playing position to improve the imbalanced shoulder.